PARENTS AND SURROUNDING INFLUENCE TO BE MULTILINGUAL - Restu Novi Sari Sudjarwo (Jurnal CULTURE (Culture, Language, and Literature Review), 2020)
Nowadays inter-ethnic marriage has become a common thing happened in Indonesia. From the inter-ethnic marriage, there is an influence to children’s language because parents will teach their children about their languages. In addition, children spend a lot of time to interact with surrounding where they live. For instance, if they live in Javanese surrounding which is known when they speak so it makes children know and follow the Javanese dialect, Another factor that influence a child to have capability to know many languages ​​besides the two factors above are the child’s intention to learn a new language and also the relation with their peers. The purpose of this research is to know what makes someone becomes multilingual and what factors that influence someone becomes multilingual are. The methods used in data collection are simak method, recording techniques, and noted techniques. In analyzing the data, the author uses the social aspect as padan method. While in the data presentation, the author uses informal method. Based on the analysis of data, there are eight respondents become multilingual because the influence of parents and surrounding where they live. Two respondents become multilingual because the influence of surrounding where they live. The results of the study are ten respondents show that they becomes multilingual because they can speak two or more languages that they got from their parents and surrounding. Then, two respondents become multilingual by the influence of their surrounding where they live. Keywords: Parents, Surroundings, Influence, Multilingual, Bilingual